Diversidad de aves acuáticas y ribereñas en época de creciente en bosque de compleo de orillares al este de Iquitos, río Itaya - Iquitos - Perú - Cometivos Salas, Marfia (2021)
Since march to june of 2018, we study diversity of acuatics and riberedge birds in season the flooded in complex edges forest to the east of Iquitos, Itaya, by canoe census. The specífic richness has of 72 species the birds, with dominace of species Passeriformes order (32 species) and Shannon diversity index of 3.255 what indicates a diversity high. Relative abundance was predominated by category the common quite with 27 species and y rare with 23 species, while what the density more high was Jacana jacana with 65 grupos y 245 ind/km2 y Brotogeris versicolurus con 43 grups and 248 ind/km2. We concluded what in complex edges forest to the east of Iquitos has diversity high acuátics and riberedges birds in season flooded with a richness the 72 species and the abundance more highs it present few species as Jacana jacana and Brotogeris versicolorus.